Magnetocaloric and Magneto-transport Properties in Polycrystalline Ni56Mn20Ga24 Heusler Alloy - Pal, D. (Journal of Scientific Research, 2023)
Polycrystalline ingots of Ni-rich Ni56Mn20Ga24 alloy were prepared by conventional arc melting procedure. The magnetocaloric and magnetotransport properties of the alloy were investigated within a temperature range from 4.2-300 K and up to a magnetic field of 8 T. A large magnetocaloric effect (∆SM ~ 29 J/Kg K) was observed in the alloy in the vicinity of magneto-structural transition temperature at a change of 5 T magnetic field. From magnetic measurements, it was observed that the martensite to austenite transition was accompanied by higher to lower magnetization in higher magnetic fields. The large entropy change was explained by considering the first-order magneto-structural transition in this alloy. A high negative magnetoresistance (⁓7 %) associated with magnetic field induced first order magneto-structural transition was also observed near room temperature due to a change of 8 T magnetic field for this alloy.